An Interactive Lifestyle Medicine Curriculum for Third-Year Medical Students to Promote Student and Patient Wellness - Rockfeld, Jennifer (MedEdPORTAL, 2020)
INTRODUCTION: Although lifestyle intervention and behavior modification are effective in the prevention and treatment of chronic disease, few medical schools provide specific training in stress management, nutrition, or physical activity. While the prevalence of chronic disease rises, medical students and physicians lack sufficient knowledge and skills to promote their patients’ as well as their own wellness across these domains. METHODS: We developed three hour-long workshops delivered to third-year medical students. We employed interactive lectures, small-group discussions, and reflective activities to teach the pillars of lifestyle medicine. These sessions focused on knowledge and skills to advance lifestyle counseling and behavior modification interventions with patients and to promote student wellness. We assessed student satisfaction with each session as well as self-perceived knowledge, skills, and attitudes toward lifestyle medicine and behavior change before and after the curriculum. RESULTS: Over 2 years, 183 students participated in the workshop series. The sessions received high ratings, with a mean of 4.2 on a 5-point Likert scale. Participating in the curriculum significantly enhanced students’ understanding of the connection between lifestyle factors and the health of patients and improved their confidence about counseling for behavioral change. DISCUSSION: Lifestyle medicine provides an evidence-based framework for teaching students about the impact of lifestyle modification on chronic disease. While receiving knowledge and skills to advance patient care in the domains of stress management, nutrition, and physical activity, students who completed this curriculum also had the opportunity to reflect on their own health promotion, which could mitigate professional burnout.